Theoretical and Numerical Studies of Dynamic Scaling of a Six-Degree-of-Freedom Laser Propulsion Vehicle - Masayuki Takahashi; Naofumi Ohnishi (International Journal of Aerospace Engineering)
To estimate the flight reactions of a full-scale vehicle from reduced-scale tests, we constructed a scaling theory for the vehicle size, input energy, moment of inertia, and pulse frequency needed to maintain dynamic equivalence between a laboratory-scale and full-scale launch of a laser propulsion vehicle. The dynamic scaling law for a single pulse was constructed using translational and angular equations of motion. The analytical scaling was confirmed for a single-pulse incident using a fluid-orbit coupling simulator for the interaction between the blast wave and the vehicle. Motion equivalence was maintained for multiple pulses by adjusting the repetition frequency of the pulse incident to correct for the effect of aerodynamic drag during the free flight of the pulse-to-pulse interval. The flight of a full-scale vehicle can be estimated for single- and multiple-pulse operations from the flight data for a small-scale vehicle using the proposed scaling theory, which provides correlations between the characteristics of small-scale and large-scale flight systems. Small-scale tests were shown to be useful in estimating the flight of a full-scale vehicle using dynamic scaling theory.